2008
DOI: 10.2169/internalmedicine.47.0639
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressive Interstitial Pneumonia Associated with Clinically Amyopathic Dermatomyositis Successfully Treated with Polymyxin B-immobilized Fiber Column Hemoperfusion

Abstract: Amyopathic dermatomyositis (ADM) is a clinical subtype of dermatomyositis, characterized by the absence of motor weakness and the presence of normal muscle enzyme levels. ADM is sometimes accompanied by interstitial pneumonia that shows a rapid progressive course associated with a poor prognosis. We describe a 70-year-old man who presented rapidly progressive interstitial pneumonia associated with clinically ADM (C-ADM); he was successfully treated with polymyxin B-immobilized fiber column (PMX) hemoperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…As an addition to a previous study reporting that CCL4 interacted (41,42). In accordance with the results of the present study, TIMP1 was also identified to be associated with interstitial pneumonia (43,44). CTSB belongs to a family of lysosomal cysteine proteases and is encoded by the CTSB gene in humans (45,46).…”
Section: Discussionsupporting
confidence: 92%
“…As an addition to a previous study reporting that CCL4 interacted (41,42). In accordance with the results of the present study, TIMP1 was also identified to be associated with interstitial pneumonia (43,44). CTSB belongs to a family of lysosomal cysteine proteases and is encoded by the CTSB gene in humans (45,46).…”
Section: Discussionsupporting
confidence: 92%
“…Fourthly, the number of courses and the time duration per one course may be critical. Reports which used PMX-DHP treated with different durations for 3-24 hours with 1-6 courses (3,4,12). While the number of courses and the time length per one course may be critical, the best protocol still remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite routine use of high dose corticosteroids and immunosuppressive agents, some cases are hard to treat. While some report the efficacy of direct hemoperfusion with a Polymyxin B immobilized fiber column (PMX-DHP) (3,4) and intravenous immunoglobulin (IVIG) (5), the efficacy and the safety of the PMX-DHP and IVIG combination are controversial. We herein report a case of rapidly progressive ILD associated with DM which survived with the administration of PMX-DHP and IVIG in addition to high dose corticosteroids and immunosuppressive agents.…”
Section: Introductionmentioning
confidence: 99%
“…Nemoto et al 9) suggested that 1 or 2 courses of adsorption for 4 hours each improved the survival of patients with sepsis. Furthermore, a recent paper has suggested that frequent applications of PMX would be effective against severe sepsis 10) . The appropriate duration and frequency of PMX administration for treatment remain unknown.…”
Section: Discussionmentioning
confidence: 99%